GAMBARAN SIKAP ERGONOMI DAN KELUHAN MUSKULOSKELETAL SELAMA PEMBELAJARAN DARING PADA MAHASISWA ILMU KEPERAWATAN DI UNIVERSITAS UDAYANA - Kelvin, I Gusti Ngurah Putu; Saputra, I Kadek; Manangkot, Meril Valentine (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2023)
Musculoskeletal disorder are often experienced by students during online learning during the Covid-19 pandemic. Purpose of this study was to find out how the description of ergonomic attitudes and musculoskeletal disorder experienced during online learning. This research is a descriptive survey research conducted on nursing students at Udayana University in April 2022 with 169 respondents selected through proportionate stratified random sampling technique. Data was collected online using ergonomic attitudes questionnaire and Nordic Body Map. The results showed that the majority of respondents aged 18-23 years were dominated by women, and 63,3% had received information on ergonomics concepts. The most widely used postures during learning are sitting on the back with the upper arm flexed 20-45o, forearm flexed 60-100o, wrist bent at an angle of more than 15o, neck slightly bent at 10-20o, and back bent at an angle 0-20o without using footrest. Musculoskeletal disorder were measured using the NBM questionnaire with the result that 62,1% had a low level of complaints and the locations most frequently complained of pain were in the upper neck (87,0%), back (81,1%), waist, hip and lower neck (80,5%). It can be concluded that the lesehan sitting position is a position that is often used during learning. This position lacks ergonomics so that it contributes as a risk factor for musculoskeletal disorder and the locations of complaints that are often felt are the neck, back, waist, and hips.